Evaluation of liver fibrosis and hepatic venous pressure gradient with MR elastography in a novel swine model of cirrhosis. Issue 3 (7th November 2013) - Huang, Steven Y.; Abdelsalam, Mohamed E.; Harmoush, Samer; Ensor, Joe E.; Chetta, Justin A.; Hwang, Ken-Pin; Stafford, R. Jason; Madoff, David C.; Avritscher, Rony
<x xml:space="preserve">Abstract</x> Purpose To assess the correlation among MR elastography (MRE) measured liver stiffness (LS), liver fibrosis, and hepatic venous pressure gradient (HVPG) in a swine model of cirrhosis. Materials and Methods Three swine served as controls, and liver fibrosis was induced in eight swine by transarterial embolization. LS and HVPG were obtained at baseline and 4 weeks (prenecropsy) following induction of liver fibrosis. Results Four weeks following the induction of liver cirrhosis, experimental animals developed an increase in HVPG of 8.0 ± 6.4 mmHg compared with 0.3 ± 1.2 mmHg for controls (P = 0.08). Over the same timeframe, mean MRE‐measured LS increased 0.82 ± 0.39 kPa for experimental swine and 0.1 ± 0.05 kPa for controls (P = 0.01). A positive correlation was observed between increases in HVPG and LS (ρ = 0.682; P = 0.02). Liver fibrosis was measured on explanted livers at 4 weeks and yielded mean fibrosis scores of 2.8 for experimental animals and 0 for controls (P = 0.0016). A positive correlation was observed between higher LS and liver fibrosis (ρ = 0.884; P = 0.0003). Conclusion MRE is a reliable noninvasive technique to measure LS in a swine model of cirrhosis. Significant positive correlations were observed between LS and HVPG as well as LS and fibrosis. J. Magn. Reson. Imaging 2014;39:590–597. © 2013 Wiley Periodicals, Inc.